Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.18632/aging.103068
|View full text |Cite
|
Sign up to set email alerts
|

Integrated data analysis reveals significant associations of KEAP1 mutations with DNA methylation alterations in lung adenocarcinomas

Abstract: INTRODUCTION Lung cancer is the leading cause of cancer deaths worldwide. Human lung cancers are classified into two major histologic types, small-cell lung cancer and nonsmall-cell lung cancer (NSCLC), the latter comprising several subtypes. Previously, lung squamous cell carcinoma was the predominant form of NSCLC, but in the last few decades it has been replaced by lung adenocarcinoma (LUAD). Moreover, LUAD is the most common type of lung cancer in women, non-smokers, and young people [1]. Epigenetic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…In order to investigate the effect of KEAP1 methylation on NRF2 modulation, we correlated each KEAP1 CpGs methylation level with the expression level of NRF2 and some of its target genes that are involved in oxidative stress, oxidation-reduction processes, and the cellular response to oxidative stress: GPX2 — Glutathione Peroxidase 2, GCLC — Glutamate-Cysteine Ligase Catalytic Subunit, TXNRD1 — Thioredoxin Reductase 1, AKR1C1 — aldo-ketoreductase family 1, PGD — Phosphogluconate Dehydrogenase, SRXN1 — Sulfiredoxin 1 , and ABCC2—ATP Binding Cassette Subfamily C Member 2 [ 26 , 27 ]. An inverse, strong correlation between KEAP1 methylation and mRNA expression levels of NRF2 and its targets was observed in both the LUAD and LUSC cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the effect of KEAP1 methylation on NRF2 modulation, we correlated each KEAP1 CpGs methylation level with the expression level of NRF2 and some of its target genes that are involved in oxidative stress, oxidation-reduction processes, and the cellular response to oxidative stress: GPX2 — Glutathione Peroxidase 2, GCLC — Glutamate-Cysteine Ligase Catalytic Subunit, TXNRD1 — Thioredoxin Reductase 1, AKR1C1 — aldo-ketoreductase family 1, PGD — Phosphogluconate Dehydrogenase, SRXN1 — Sulfiredoxin 1 , and ABCC2—ATP Binding Cassette Subfamily C Member 2 [ 26 , 27 ]. An inverse, strong correlation between KEAP1 methylation and mRNA expression levels of NRF2 and its targets was observed in both the LUAD and LUSC cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this idea, our group recently observed that an evaluation of each CpG methylation status at the promoter region of KEAP1 by pyrosequencing provides more information with a possible translational utility than the conventional semi-quantitative approach used until now [ 25 ]. Secondly, only some CpGs located at the promoter region and not all CpGs of KEAP1 that could exert a strong regulatory effect on its transcription and protein levels have been yet investigated [ 26 ]. As for the intragenic CpGs island of many cancer-related genes, the function of CpGs located in the gene body of KEAP1 has been poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Log rank test P<0.05 was used as the cutoff for signi cance. The method of analysis has been discussed in a previous study (5).…”
Section: Survival Analysismentioning
confidence: 99%
“…In previous studies, we identi ed gene signatures that are regulated by the KEAP1-NRF2 pathway in lung adenocarcinoma (LUAD) and head and neck squamous cancer (HNSC) (4)(5)(6). In the current study, we used the genomics, and transcriptomics data of the ESCA cohort from TCGA to identify a gene signature regulated by the KEAP1-NRF2 pathway in ESCA.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with their wide-ranging roles, some of the KLHL or KBTBD proteins are associated with somatic diseases or linked to hereditary disease [ 6 , 7 ]. Downregulation of KEAP1 ( KLHL19 ), the most well-studied KLHL family gene, is implicated in many types of cancer [ 6 , 8 ], and cancer-associated mutation of other KLHL family genes has been described [ 5 ]. Among the other diseases in which KLHL family proteins are implicated are myopathies [ 9 , 10 ], diabetes [ 11 ], pseudohypoaldosteronism (a mineral transport disorder) [ 12 ], and cardiac dysfunction [ 13 ].…”
Section: Introductionmentioning
confidence: 99%